2012
DOI: 10.1038/leu.2012.123
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pretransplant minimal residual disease after cord blood transplantation for childhood acute lymphoblastic leukemia in remission: an Eurocord, PDWP–EBMT analysis

Abstract: To address the prognostic value of minimal residual disease (MRD) before unrelated cord blood transplantation (UCBT) in children with acute lymphoblastic leukemia (ALL), we analyzed 170 ALL children transplanted in complete remission (CR) after myeloablative conditioning regimen. In all, 72 (43%) were in first CR (CR1), 77 (45%) in second CR (CR2) and 21 (12%) in third CR (CR3). The median interval from MRD quantification to UCBT was 18 days. All patients received single-unit UCBT. Median follow-up was 4 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
33
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 46 publications
10
33
1
Order By: Relevance
“…9,22 However, in contrast to these previous reports, in the cord-blood group, the overall mortality and rate of relapse were similar among patients with minimal residual disease and those without minimal residual disease. These observations are not entirely consistent with previous reports regarding transplants from cord-blood donors, [23][24][25] in which a higher risk of relapse and a lower rate of leukemia-free survival was seen among patients with minimal residual disease than among those without minimal residual disease.…”
Section: Discussioncontrasting
confidence: 52%
“…9,22 However, in contrast to these previous reports, in the cord-blood group, the overall mortality and rate of relapse were similar among patients with minimal residual disease and those without minimal residual disease. These observations are not entirely consistent with previous reports regarding transplants from cord-blood donors, [23][24][25] in which a higher risk of relapse and a lower rate of leukemia-free survival was seen among patients with minimal residual disease than among those without minimal residual disease.…”
Section: Discussioncontrasting
confidence: 52%
“…[3][4][5][6][7][8] Although consolidative therapy with HCT can cure some patients with persistent MRD, 7,14,15 most studies suggest that the majority of these patients will relapse post HCT. 3,[6][7][8] The idea that leukemia-free survival would be improved if pre-transplant MRD can be eliminated has scientific rationale, but the theory has not been formally tested. Whether pre-HCT MRD represents a patient who is inadequately treated, or one who has underlying high-risk biology that is predetermined to fail HCT, is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that identifying minimal residual disease (MRD) prior to HCT is the strongest predictor of treatment failure. [3][4][5][6][7][8] Whether eliminating MRD prior to HCT will influence post-HCT outcomes, particularly with regard to reducing relapse, has not yet been established. However, this approach is not without risks, as additional chemotherapy in patients who have already achieved remission could lead to toxic complications that may preclude proceeding to HCT or increase peri-transplant toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, these studies uniformly found excellent long-term outcomes for patients without detectable MRD (that is, 'MRD À ' patients) undergoing myeloablative AlloHCT, with 2-5 year estimates of EFS, relapse-free survival and OS often in the 70-80% range, and more recent series suggesting even better outcomes. [29][30][31][34][35][36][37][39][40][41][42][43][46][47][48][49] Almost without exception, the outcomes for patients with detectable MRD (that is, 'MRD þ ' patients) were significantly inferior, with long-term estimates of EFS of 0-30% and OS of 30-50%, respectively. Although data are more limited for AutoHCT, available information suggests that MRD À patients may have relatively good disease control that appears to approach that seen after AlloHCT, at least in the subset of leukemias that do not harbor the Philadelphia chromosome; on the other hand, MRD þ ALL patients experience exceedingly high rates of relapse after AutoHCT.…”
Section: The Concept and Determination Of Mrdmentioning
confidence: 99%
“…53,57,61,62 However, MRD appears to bear significance as an independent prognostic marker, as suggested by multivariate regression modeling in many of the studies. [27][28][29]36,37,39,[42][43][44][47][48][49]53,54,57,[59][60][61] The association between MRD and risk of BM relapse is likely 'dose-dependent' in ALL 27,28,36,37,41,42,44,47,63 and, possibly, AML, 53,54,60 while MRD assessments may fail to predict extramedullary relapse accurately. 32,45 Interestingly, evidence from logistic regression models suggests that the relative level of MRD has more impact on survival in ALL than in AML.…”
Section: The Concept and Determination Of Mrdmentioning
confidence: 99%